Mengukur Tingkat Spiritualitas Siswa di SMP Kristen Makedonia Ngabang:: Menggunakan Youth Spirituality Scale (YSS) - Wiyono, Slamet; Hanock, Edward E.; Danny; Pitriani, Sinta (MANTHANO: Jurnal Pendidikan Kristen, 2025)
Abstract: Christian education plays a vital role in shaping students' spirituality amidst modern challenges. This study assesses the spirituality levels of students at SMP Kristen Makedonia Ngabang across four dimensions: spiritual beliefs, moral behavior, religious practices, and gratitude, employing a quantitative descriptive approach with the Youth Spirituality Scale (YSS) on 26 ninth-grade students. The results reveal that the students' spirituality levels fall under the very high category (average score: 102.42), with Spiritual Beliefs and Gratitude as the most dominant dimensions, reflecting strong connections with God and positive life attitudes. However, weaknesses in honesty within the Moral Behavior dimension highlight the need for strengthening character education. This study affirms the effectiveness of holistic Christian education through activities such as prayer, worship, and mentoring. Recommendations include integrating spiritual values into curricula, adopting personalized approaches, and fostering moral discussions to support student development. Future research is suggested to explore the long-term impacts of spirituality on students' psychosocial and academic outcomes. Abstrak: Pendidikan Kristen berperan penting dalam membentuk spiritualitas siswa di tengah tantangan modern. Penelitian ini mengevaluasi tingkat spiritualitas siswa SMP Kristen Makedonia Ngabang melalui empat dimensi: keyakinan spiritual, perilaku moral, praktik keagamaan, dan rasa syukur, menggunakan metode kuantitatif deskriptif dengan Youth Spirituality Scale (YSS) pada 26 siswa kelas 9. Hasil menunjukkan tingkat spiritualitas siswa berada pada kategori sangat tinggi (rata-rata 102,42), dengan dominasi pada dimensi Keyakinan Spiritual dan Rasa Syukur, yang mencerminkan hubungan siswa yang kuat dengan Tuhan serta sikap hidup positif. Namun, kelemahan pada aspek kejujuran dalam Perilaku Moral mengindikasikan perlunya penguatan pendidikan karakter. Penelitian ini menegaskan keberhasilan pendidikan Kristen holistik melalui kegiatan doa, ibadah, dan mentoring. Direkomendasikan integrasi nilai spiritual dalam kurikulum, pendekatan personal, dan diskusi moral untuk pengembangan siswa. Penelitian lanjutan disarankan untuk mengeksplorasi dampak spiritualitas terhadap psikososial dan akademik siswa.